The engineer’s instruction to postpone the boundary wall work under section 7 of BOQ at BRACU new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the engineer’s instruction to postpone the boundary wall work under section 7 of BOQ at BRACU new campus project.